2022
DOI: 10.1177/20406207221127532
|View full text |Cite
|
Sign up to set email alerts
|

Avatrombopag for the treatment of thrombocytopenia post hematopoietic stem-cell transplantation

Abstract: Background: Thrombocytopenia post hematopoietic stem-cell transplantation (HCT) usually contributes to poor outcomes with no standardized treatment. Eltrombopag and romiplostim can be feasible for post-HCT thrombocytopenia, but the use of avatrombopag has not yet been evaluated. Objectives: We aimed to evaluate the efficacy and safety of avatrombopag treatment in patients diagnosed with post-HCT thrombocytopenia. Design: In this retrospective study, we evaluated the efficacy and safety of avatrombopag treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…Moreover, the CRR was in a range of 50%–72% among PIT, SFPR, and PGF in adults ( 6 ). Regarding avatrombopag for post-HSCT thrombocytopenia, there were only a few studies published to date, and all of these studies were performed in only the adult population ( 18 , 21 ). Zhou et al reported that the ORR was 68.9% while CRR was 39.3% using avatrombopag for the treatment of delayed platelet engraftment and SFPR ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, the CRR was in a range of 50%–72% among PIT, SFPR, and PGF in adults ( 6 ). Regarding avatrombopag for post-HSCT thrombocytopenia, there were only a few studies published to date, and all of these studies were performed in only the adult population ( 18 , 21 ). Zhou et al reported that the ORR was 68.9% while CRR was 39.3% using avatrombopag for the treatment of delayed platelet engraftment and SFPR ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding avatrombopag for post-HSCT thrombocytopenia, there were only a few studies published to date, and all of these studies were performed in only the adult population ( 18 , 21 ). Zhou et al reported that the ORR was 68.9% while CRR was 39.3% using avatrombopag for the treatment of delayed platelet engraftment and SFPR ( 18 ). Zhu et al further investigated the effects of avatrombopag combined with MSC for post-HSCT thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…71 Platelet transfusions remain the backbone of therapy, while boost doses of CD34 þ cells have been used in PGF. 68 Some retrospective studies, as seen in ►Table 2, examined TPO-RA's role in this context, with reported response rates varying from 39.3 to 83.3%, [72][73][74][75][76][77][78][79][80][81][82][83] whereas results from few prospective studies are mostly conflicting. 84,85 Both ROMI and EP, and recently avatrombopag, proved to be as safe and effective and possibly cost-effective in comparison to transfusions in thrombocytopenia after allo-HSCT and PGF.…”
Section: Thrombopoietin Receptor Agonists In Allogeneic Hematopoietic...mentioning
confidence: 99%